Development of medication reminder WhatsApp Bot application to improve medication adherence in pregnant women with hypertension - Kurniasih, Hesti; Winarso, Septerina Purwandani; Sartika, Qona Lutfi (MEDISAINS, 2024)
Background: Pregnant women's compliance with taking medication regularly is essential and supports the success of therapy. If pregnant women do not comply with taking medication, this can hurt the development of the disease and cause unexpected complications. Non-communicable diseases cause most cases of death in pregnant women. This is the basis for researchers to create a medication reminder system.Purpose: This research aims to develop a WhatsApp Bot application, WhatsApp Bot, that reminds users when to take medication. Method: This study employed Research and development, which consisted of four stages: Literature Study, Development Stage, Validity Expert, and Trial.Results: A system that health workers can use in primary health facilities to remind them when to take medication has been successfully created. Performance test of the medication reminder system with a high % accuracy rate of 98% (MAPE value 9.05%).Conclusion: This application is beneficial for pregnant women to remind them to take medication to increase compliance.